PENERAPAN MODEL PROBLEM BASED LEARNING DALAM PEMBELAJARAN PELUANG DI KELAS VIII SMP NEGERI 1 MODOINDING - Mangobi, James; Monoarfa, Jorry; Momongan, Novita (Universitas Negeri Manado, 2020)
ABSTRACT. This research aims to determine whether the student learning outcomes on probability lesson Â taught by using the Problem Based Learning model were more than those whom Â taught using the direct learning model. This research is categorized as quasi-experimental research, with a Posttest Only Control Group Design. The subject in this research were students of class VIII B and VIII C of SMP Negeri 1 Modoinding with a total of 40 students. The posttest score results were prosesed from students of the experiment and control classes. The results showed that the learning outcomes of students taught using the PBL model were more than the learning outcomes of students who were taught using the direct learning model.Â Key Words: Learning Outcomes, PBL, Probability